2019
DOI: 10.1177/1455072519835710
|View full text |Cite
|
Sign up to set email alerts
|

Declining alcohol consumption among adolescents and schools in Stockholm, 2010–2016

Abstract: Aims: The principle aim of this study was to investigate changes in alcohol consumption among adolescents in Stockholm from 2010 to 2016. A further aim was to investigate whether there are divergent or similar trends in alcohol consumption among elementary schools in Stockholm from 2010 to 2016 and, if there are diverging trends, to examine how the differences might be explained. Methods: Data were analysed using multilevel mixed effects linear regression, in which individual students represented one level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Our finding that close and friendly relationships between adolescents and their parents may impact adolescents' non-drinking expands findings from previous survey studies, suggesting stricter parental monitoring and rules as one explanation for the downward trend in drinking among adolescents [8,9,20,27,28]. In the current study, adolescents described their parents as monitoring, and emotionally close and supportive.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our finding that close and friendly relationships between adolescents and their parents may impact adolescents' non-drinking expands findings from previous survey studies, suggesting stricter parental monitoring and rules as one explanation for the downward trend in drinking among adolescents [8,9,20,27,28]. In the current study, adolescents described their parents as monitoring, and emotionally close and supportive.…”
Section: Discussionsupporting
confidence: 85%
“… who hypothesise that changes in the social position of alcohol are related to how its perceived negative effects do not fit with an increasingly health‐oriented youth culture, and also to changes in technology, social norms and family relationships. As in a recent qualitative study from Sweden , our findings indicate that the cultural position of drinking may have changed among young adolescents, towards a situation where alcohol has less importance in peer networks and where alcohol use is devalued . They correspond with studies describing little peer pressure to drink and room for individual choice to drink alcohol or not , and non‐drinkers actively redefining and influencing the role that drinking has in social situations .…”
Section: Discussionsupporting
confidence: 82%
“…Since then, several studies in Sweden have examined whether declines in youth alcohol consumption are occurring collectively across the population using school survey data, but have obtained mixed results. Some find evidence of collectivity , whereby youth declines in alcohol consumption are proportionate across light‐, moderate‐ and heavy‐drinking 11–15 , 15–16 and 17–18‐year‐olds . Further support for collectivity theory comes from a Norwegian study that showed that alcohol consumption increased among all Norwegian 16–17‐year‐old drinkers between 1995 and 2011, in line with population trends .…”
Section: Introductionmentioning
confidence: 96%
“…To date, examinations of collectivity have primarily occurred in Sweden , with one study in Norway . Further international work examining whether reductions in youth drinking occur collectively in a broader range of contexts and countries is now required to understand the international public health implications.…”
Section: Introductionmentioning
confidence: 99%
“…In his research article in this issue, Carlson (2019) discusses the almost 45% decline in total alcohol consumption among ninth-grade students in Stockholm between 2010 and 2016. Carlson explains the decline by more restrictive parental attitudes towards alcohol, and, more importantly, by decreasing alcohol consumption among the students’ peers.…”
Section: Self-evident Presence Of Societymentioning
confidence: 99%